Numerical Mathematics and Advanced Applications 2011: Proceedings of ENUMATH 2011, the 9th European Conference on Numerical Mathematics and Advanced Applications, Leicester, September 2011 - Cangiani, Andrea (SpringerLink Bücher, 2013)
Part I A Posteriori Error Estimation and Adaptive Methods -- Part II Computational Electromagnetics -- Part III Computational Methods -- Part IV Convection, Diffusion, Conservation, and Hyperbolic Systems -- Part V Discontinuous Galerkin Methods -- Part VI Finite Element and Finite Volume techniques -- Part VII Fluid Mechanics -- Part VIII High Performance Computing -- Part IX Multiscale Modeling and Simulations -- Part X Preconditioners and Solvers -- Part XI Uncertainty, Stochastic Modelling, and Applications.